Physical and chemical characteristics of controlled release compound fertiliser - Hanafi, M.M; Eltaib, S.M; Ahmad, M.B (Elsevier, 2000)
Fertility management of soil is greatly improved by supplying nutrients according to the physiological needs of plants. Controlled release (CR) compound fertiliser is expected to give all major nutrients to plants. The compound fertiliser (15% N, 2% P, 16% K, 4% Ca, 1% Mg, and 0.1% Cu) was prepared in the laboratory using a granulation machine and was coated using polyvinyl chloride (PVC), polyacrylamide (PA), natural rubber (NR), and polylactic acid (PLA). The coated compound fertilisers were characterised using Fourier transform infrared spectroscopy (FT-IR), differential scanning calorimetry (DSC), thermogravimetric (TGA) and differential thermogravimetric (DTG) analyses, and scanning electron microscopy (SEM). Similar number of peaks were observed in the DSC as in TGA and DTG for the coated compound fertilisers. With the exception of PVC (four peaks, including one exothermic peak), all coated compound fertilisers exhibited three broad endothermic peak. Thermal-oxidative stability, as determined at 300°C, decreased in the order: NR>PLA>PVC>PA. In contrast, the thickness of the coating layer on the compound fertiliser granules, determined by SEM, gave PVC compound coated fertiliser the highest value of 3.04 μm, and the lowest was obtained by PA (2.04 μm). Variation in the characteristics of the polymers would be utilised in producing CR compound fertiliser that fit the requirements of growing plants.